Obesity in children and adolescents as a trigger factor for dental caries, literature review - Karen Ruiz Mena; Samantha Trávez Pacheco; Olivia Toalombo Puma; Esteban Sotelo Garzon; Ana Armas Vega (Asociación Latinoamericana de Odontopediatría, 2019)
Objective: To establish the relationship of obesity in children and adolescents with the presence of dental caries. Materials and methods: A bibliographic review of PUBMED database was carried out, using terms like, Caries, Obesity, Child, adolescent with AND as a boolean connector. All articles published between 2013 and 2018 were taken into account. 40 articles were found, 29 later excluded because they referred variables not considered in the study. The remaining 11 articles were reviewed and the main findings synthesizad. Results: The literature reviewed does not suggest an association between obesity and the presence of caries. A strong influence of low weight with dental caries was identified. Conclusions: Dental caries in children and adolescents does not suggest a relationship with weigth gain.